Understanding child poverty in developing countries: measurement and analysis - Dercon, S (Palgrave Macmillan, 2012)
Childhood, and the extent and consequences of childhood poverty, have a central place in the study of development. In many economies of Asia and Latin America, where growth has picked up considerably in recent years, the patterns of growth and the extent and nature of inclusion of poor people are crucially important for the type of society that will be produced for the next generation. More specifically, the educational and health opportunities for children who are currently poor, as well as the nature of their social inclusion and their general well-being, will determine their chances of partaking fully in this future society. In several sub-Saharan African countries, despite recent growth successes, sustained growth is still largely elusive, and current child poverty, with its cumulative effects on destitution, may undermine the possibility of economic growth in the future. Recent research has highlighted the cumulative consequences of childhood poverty and deprivation. For example, a meta-analysis of the effects of early childhood nutritional deficiency and poverty has highlighted its serious consequences for a variety of outcomes, including school achievement and earning potential in later life (Grantham-McGregor et al. 2007).